Legal Implication of Unregistered Polygamous Marriages Without Court Permission In Negeri Sembilan - Laila Salikin Wan Ibrahim; Norsuhaida Che Musa (USIM Press, 2024)
All Muslim countries, including Malaysia, have struggled with the issue of polygamous marriages. Due to the instability of families in society caused by individuals who misuse the authority granted by the Quran, a special rule regarding polygamy has been enacted in the Islamic Family Law. Cases involving polygamous marriages without court permission are one kind of case that arises regularly in the Syariah High Court. In keeping with the goals of Syariah, the court introduced a method that that fundamentally preserves each polygamous couple's rights and obligations. If a man is previously married, he cannot marry another woman without the court's approval. The principal aim of this study is to increase consciousness regarding the need to safeguard the rights of co-wives and their children in unregistered polygamous marriages. Being unaware of unregistered polygamous marriages puts the majority of co-wives and children in this position at risk of persecution. Additionally, this article aims to investigate the legal implications of unregistered polygamous marriages without court permission for co-wives and children in Negeri Sembilan. Determining and assessing the level of knowledge and practice of polygamy among Malaysian polygamous spouses is essential to safeguarding the rights that ought to be obtained. Thus, this research refers to actual case law from Syariah High Court, Negeri Sembilan and the enactment of the Islamic Family Law (Negeri Sembilan) Enactment 2003, which will determine how compatible they are. In doing so, to avoid misconceptions under Islamic Law, a husband should register a polygamous marriage to support legal co-wives. Addressing maintenance, inheritance and legitimacy of children requires formal registration for a legally recognized marriage certificate in Malaysian law.